An investigation analysing the effects of introducing workplace fun on level of job satisfaction and well-being on middle level management in India: a case of Rosy Blue Diamond and Orra Jewellery - Mehta, Ria (2014)
Work pressure on the employees is increasing with rising competition. The motive of the paper is to understand the impact of introducing fun activities on overall employee satisfaction and welfare. This study makes an attempt to study these aspects in relation to the Indian jewellery industry. Here two organizations have been selected who fulfils the case requirement. Data for the study was collected from 100 participants, from which 50 were from Rosy Blue Diamonds and rest 50 being from Orra Jewellery this data was collected using a questionnaire. Responses were based on a five-point scale (1=Strongly Disagree to 5=Strongly Agree) so as to facilitate statistical analysis. Results obtained from both the organizations which has recently introduced fun at workplace show that fun activities has improved employee satisfaction and well-being by far. Resulting in overall positive environment and happy employees, reduction in stress and absenteeism were witnessed to be evident. However, evident distinction in opinion was spotted while analysing results of few of the variables.